2003
DOI: 10.1530/rep.0.1250657
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lysyl oxidase and effect of copper chloride and ammonium tetrathiomolybdate on bovine ovarian follicle granulosa cells cultured in serum-free media

Abstract: Subfertility that will respond to appropriate copper supplementation is a widespread problem in the UK dairy herd and, although characterized by reduced or absent oestrus and reduced conception rates, the exact cause remains unknown. The aim of this study was to investigate the expression of mRNA for the copper-dependent enzyme, lysyl oxidase, and the effect of copper and/or copper chelating thiomolybdates on FSH-induced differentiation of bovine granulosa cells cultured in serum-free media. Expression of lysy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…During hypocuprosis, the activity of the enzyme lysyl oxidase (LOX), which is Cu dependent, suffers a considerable reduction, thereby causing a severe perturbation in the growth rate of pre-ovarian follicles, leading to reduction in the secretion of ovarian estradiol, a lower peak of estradiol in the pre-ovarian follicle, which is an endocrine sign that responsible for estrus induction, which in turn leads to perturbations of estrus and ovulation respectively (Kendall et al 2003) During Cu deficiency, the activity of the enzyme 15'15' dioxygenase is reduced; it is Cu dependent and responsible for the rupture of the central double bond of the carbon 15 of the carotene molecule, an indispensable factor in the formation of vitamin A (Izaguirre & Shimada 2001). Sharma et al (2003) have reported a correlation of vitamin A with the Cu serum status of the animals with a marked significant deficiency of vitamin A in the Cudeficient animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During hypocuprosis, the activity of the enzyme lysyl oxidase (LOX), which is Cu dependent, suffers a considerable reduction, thereby causing a severe perturbation in the growth rate of pre-ovarian follicles, leading to reduction in the secretion of ovarian estradiol, a lower peak of estradiol in the pre-ovarian follicle, which is an endocrine sign that responsible for estrus induction, which in turn leads to perturbations of estrus and ovulation respectively (Kendall et al 2003) During Cu deficiency, the activity of the enzyme 15'15' dioxygenase is reduced; it is Cu dependent and responsible for the rupture of the central double bond of the carbon 15 of the carotene molecule, an indispensable factor in the formation of vitamin A (Izaguirre & Shimada 2001). Sharma et al (2003) have reported a correlation of vitamin A with the Cu serum status of the animals with a marked significant deficiency of vitamin A in the Cudeficient animals.…”
Section: Discussionmentioning
confidence: 99%
“…There are various clinical symptoms associated with hypocupremia, even though it has been suggested that reproductive problems are the principal manifestation of hypocuprosis in adult animals (Kendall et al 2003, Ahola et al 2005. Reports have shown a negative correlation between cupremia in the range of 9.8±1.0 to 14.0±0.9 µmo/L and reproductive indicators, as much in animals with spontaneous cupremia as with the induced form.…”
Section: Introductionmentioning
confidence: 99%
“…Similar phenomena were observed in other types of cells cultured in vitro. For example, ammonium tetrathiomolybdate at 10 µg/ml resulted in a marked reduction in cellular clumping, and at 100 µg/ml and higher in absence of clumping [Kendall et al 2003]. This showed that ammonium tetrathiomolybdate can prevent induced differentiation of bovine granulosa cells cultured in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Zygotes were flushed from oviducts 18 h post-hCG injection, removed their cumulus cells by a brief exposure to 0.01% hyaluronidase, and then cultured in 50 µl droplets of potassium simplex optimized medium (KSOM) [Lawits and Biggers 1993] with 0,5,10,20,40,80,120, and 160 µg/ml of molybdenum (sodium molybdate dihydrate) covered under mineral oil at 377°C and 5% CO 2 in air for 5 d. The selection of those doses were based on previous reports [Kendall et al 2003;Kendall et al 2006;Kolesarova et al 2009] and the concentration that humans may be exposed [Huang et al 2011].…”
Section: Embryos and Treatmentmentioning
confidence: 99%
“…TGF-1 and GDF9 increase lox mRNA expression in rat granulosa cells (Kendall et al, 2003). The GDF9-induced preantral follicular growth in vitro involves increased mural granulosa cell lox mRNA expression (Assou et al, 2010), and similarly the investigations on rat granulosa cells showed that lox transcripts were significantly suppressed 48h after eCG injection compared with untreated controls (Jiang et al, 2010).…”
Section: The Putative Markersmentioning
confidence: 96%